Application of Retort Pouch Sterilization Technology to DD Satoe Packaged Chili Sauce Surabaya - Ali, Dego Yusa; Estiasih, Teti; Yulianingsih, Rini; Puspita, Riska; Adila, Lutfia; Praditya, Brilliant (Journal of Innovation and Applied Technology, 2023)
People in Indonesia are usually consuming commercial packaged of home-made chili sauce, which is mostly produced by MSMEs. UD Dede Satoe produce chili sauce using preservation techniques with aseptic packaging. The weakness of this technique is that aseptic conditions  are  not  fully  adequate  for  preservation. Nowadays, people awareness to health and food safety are increasing. To meet market demand for packaged chili products without preservatives addition, UD DD Satoe is trying to change the process from aseptic packaging to sterilizing packaged chili sauce using retort technology. The evaluation results show that retort pouch sambal can last for 1 year without the addition of preservatives. This result was proven to be better than the preservation method of making semi-dry packaged chili sauce, because it can maintain the color, taste and texture of the chili sauce.